2018
DOI: 10.1136/bmjoq-2017-000193
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of community pharmacy error rates in the USA: 1993–2015

Abstract: ImportanceWhile much is known about hospital pharmacy error rates in the USA, comparatively little is known about community pharmacy dispensing error rates.ObjectiveThe aim of this study was to determine the rate of community pharmacy dispensing errors in the USA.MethodsEnglish language, peer-reviewed observational and interventional studies that reported community pharmacy dispensing error rates in the USA from January 1993 to December 2015 were identified in 10 bibliographic databases and topic-relevant grey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…The linear regression of formulations (1–5) demonstrated that the data had the same trend and similar r 2 values ( Supplementary Figure S1 ), while the t -test significance of results was calculated by comparing the equations reported earlier ( Supplementary Information ) [ 68 ].…”
Section: Resultsmentioning
confidence: 87%
“…The linear regression of formulations (1–5) demonstrated that the data had the same trend and similar r 2 values ( Supplementary Figure S1 ), while the t -test significance of results was calculated by comparing the equations reported earlier ( Supplementary Information ) [ 68 ].…”
Section: Resultsmentioning
confidence: 87%
“…Various rates of dispensing errors ranging between 0.04 and 55% have been reported in the literature. 13 - 23 However, it is challenging to compare reported rates of dispensing errors directly across studies, owing to differences in study design, methodology, operational procedures, denominators (such as total numbers of prescriptions, numbers of dispensed doses, or numbers of prescribed medications), as well as dispensing practices. Moreover, although this rate is low, it should still be considered because it can translate into many errors due to the high volumes of medications dispensed each day by community pharmacies.…”
Section: Discussionmentioning
confidence: 99%
“… 12 The rates of dispensing errors were estimated to range between 0.04-55% depending on the study setting, method, and operational definitions. 13 - 23…”
Section: Introductionmentioning
confidence: 99%
“…The dispensing error rate in US community pharmacies has been reported to be 1.5%. 129 With 5.8 billion prescriptions dispensed in the United States in 2018, nearly 240 000 dispensing errors occur daily. 76 Automated dispensing, as already successfully demonstrated by a fully robotic hospital pharmacy in San Francisco, can bring that error rate to zero.…”
Section: Data Synthesismentioning
confidence: 99%